A water-soluble, small molecular fluorescence probe based on 2-(2′-hydroxyphenyl) benzoxazole for Zn2+ in plants. Issue 45 (7th November 2018) - Shang, Yuting; Zheng, Shuwen; Tsakama, Madalitso; Wang, Miao; Chen, Weihua
Graphical abstract: Highlights: Reliable synthesis of the probe ZFP whose structure was confirmed by X-ray analysis. The probe shows high sensitivity and selectivity toward zinc ions against other metal ions. Unique sensing mechanism with perturbation of enol/keto tautomer emission. Excellent biocompatibility to ensure the probe to easily transport in both xylem and phloem of plants. Abstract: A water-soluble, small molecular zinc fluorescence probe (ZFP) based on 2-(2′-hydroxyphenyl) benzoxazole was prepared. It exhibited high selectivity and sensitivity to Zn 2+ than the other metal ions. The highest fluorescence enhancement was observed in the presence of Zn 2+ owing to the inhibition of excited-state intramolecular proton transfer (ESIPT). Furthermore, fluorescence imaging experiments confirmed that ZFP can be used to monitor Zn 2+ in biological systems.